The Impact of Environmental Pollution on Human Health: A Medical Perspective - Arzij, Bahaa Abd Alsattar Mohammed; Shawqi, Bilal Hassan; Hassan, Omar Hamad; Tawfiq, Obaida Khalid Ismail; Jasem, Hdwan Taha (American Journal of Biodiversity, 2025)
Environmental pollution is a growing global concern with significant implications for human health. Despite extensive research, a critical knowledge gap remains in understanding the long-term effects of exposure to pollutants across multiple environmental sources. This study employs cross-sectional epidemiological analyses focusing on air, water, soil, and biodiversity in Kosovo to assess health risks. By integrating biomarker assessments, dose-response evaluations, and gene-environment interaction studies, the research identifies key biological mechanisms linking chronic exposure to pollution-related diseases. Findings indicate a strong correlation between pollutant exposure and increased risks of respiratory, cardiovascular, and neurological disorders. The results underscore the urgent need for stricter environmental policies and improved pollution monitoring strategies. This study contributes to the development of targeted public health interventions and policy recommendations to mitigate pollution-related health risks.